Associations between body mass index and clinico‐pathological characteristics of papillary thyroid cancer. (11th December 2012) - Kim, Hye Jeong; Kim, Na Kyung; Choi, Ji Hun; Sohn, Seo Young; Kim, Se Won; Jin, Sang‐Man; Jang, Hye Won; Suh, Sunghwan; Min, Yong‐Ki; Chung, Jae Hoon; Kim, Sun Wook
Summary: Objective: Epidemiological studies have demonstrated that excess weight increases the risk of thyroid cancer. However, the associations between excess weight and prognostic factors for thyroid cancer are uncertain. We evaluated the relationships between body mass index (BMI) and clinico‐pathological features and outcomes of papillary thyroid cancer (PTC). Patients and Methods: Retrospective analysis of 2057 patients with PTC was performed. Patients were grouped according to BMI (underweight, normal weight, overweight and obesity)‐based World Health Organization standardized categories. Logistic regression models were used to assess the relationships between BMI and clinico‐pathological features of PTC. A Cox proportional hazards model was used to examine the association between BMI and disease recurrence. Results: A 5‐kg/m 2 increase in BMI was associated with PTC tumours larger than 1 cm [odds ratio (OR) 1·31, P  < 0·001], with microscopic extrathyroidal invasion (OR 1·23, P  = 0·006), and with advanced tumour‐node‐metastasis (TNM) stage (OR, 1·30, P  = 0·003), which is independent of confounding variables such as gender, age, serum TSH, total cholesterol and fasting glucose level. The multivariate‐adjusted OR [95% confidence intervals (CI)] in the overweight (25·0–29·9 kg/m 2 ) and obese (BMI ≥ 30) groups for tumours larger than 1 cm were 1·41 (1·10–1·81) and 2·17 (1·23–3·82), respectively, compared to the normal weight group (BMI 18·5–24·9). The multivariate‐adjusted OR (95% CI) for microscopic extrathyroidal extension in the obesity group was 1·88 (1·06–3·32), and the OR for advanced TNM stage in the overweight group was 1·35 (1·02–1·79) compared to the normal weight group. During follow‐up (median, 84 month; range, 1–185), 43 patients (2·1%) experienced recurrence. There were no significant differences in recurrence of PTCs among BMI groups. Conclusions: Higher BMI was strongly associated with larger tumour size, extrathyroidal invasion and advanced TNM stage of PTCs. However, there was no difference in recurrence rate among BMI groups. This study suggests that excess weight is associated with aggressive features of PTCs. Further studies with long‐term follow‐up are needed to confirm this finding.